"Era como si esas casas no encajaban con la comunidad": Caminatas with Futurxs Maestrxs Bilingües in a Gentrifying Latinx Community. Issue 1 (2nd January 2021) - Heiman, Daniel; Bybee, Eric Ruíz; Rodríguez, Haydeé Marie; Urrieta, Luís
ABSTRACT: Although direct engagement with neighborhood espacios deepens student understanding, less is known about the benefits of this approach to bilingual teacher preparation programs. Our article addresses this gap by highlighting community walks, or caminatas, as a pedagogical approach with futurxs maestrxs bilingües (FMBs). Specifically, we propose an espacio emergente in the preparation of FMBs, and we examine how two Latinx professors used caminatas through a historically Latinx community in a rapidly gentrifying area to support the development of students' critical consciousness. Our findings indicate that the caminatas allowed students to historicize the local neighborhood, interrogate power and their own deficit conceptions of minoritized communities, critically listen to the sounds and voices of the community, and experience discomfort in nuanced ways. We argue that caminatas deepen FMBs' understanding of community assets and are an innovative way to support the fourth goal of preparing FMBs: developing critical consciousness.